THE ROLE OF MANAGERIAL OWNERSHIP IN MODERATING THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND PROFITABILITY ON COMPANY VALUE (STUDY OF CONSUMER GOODS INDUSTRY COMPANIES FOR THE 2019-2022 PERIOD) - Alfia Andriyani Andriyani; Hadiah Fitriyah (Antis Publisher, 2025)
Objective: This study aims to prove the role of managerial ownership in moderating the influence of CSR and profitability on company value. Method: The research approach is quantitative with secondary data in the form of annual reports of manufacturing companies in the consumer goods sector listed on the IDX for the period 2019-2022. Purposive sampling was used to select a total of 14 companies over 4 periods, with a total sample of 56. The analysis technique used multiple linear regression, moderating regression analysis (MRA) assisted by SPSS 26 software. Result: The findings prove that the profitability variable has a positive effect on company value, but the corporate social responsibility disclosure variable has no effect on company value. Furthermore, the moderating variable of managerial ownership has no effect. Novelty: The novelty of this study lies in its focus on the moderating role of managerial ownership, which has not been shown to have an effect on the relationship between CSR, profitability, and company value, offering new insights into corporate governance.